Скатерти, одеяла, пледы, подушки - Олянишина Наталья Юрьевна (Энциклопедия вязания, 2013)
Экземпляры: ф.1 (20230517) / Инвентарный номер: 63568 / Цена: / Сис.шифр: 37.248 / Авт.знак: О-56 / ГРНТИ: 75.35 / ББК: 37.248